ChemInform Abstract: Linear Infinite Cadmium Chains in CaAu4Cd2 and Other Intermetallics with YbMo2Al4‐Type Structure. Issue 29 (1st July 2013) - Tappe, Frank; Matar, Samir F.; Schwickert, Christian; Winter, Florian; Gerke, Birgit; Poettgen, Rainer
Abstract The new compounds CaAu4Cd2, SrAu4Cd2, and EuAu4.8Cd1.2 are synthesized from the elements (sealed Ta tubes, 800 mbar Ar, 923 K, 3 h).